Current Perspectives on the Role of TNF in Hematopoiesis Using Mice With Humanization of TNF/LT System - Gogoleva, Violetta S.; Atretkhany, Kamar-Sulu N.; Dygay, Arina P.; Yurakova, Taisiya R.; Drutskaya, Marina S.; Nedospasov, Sergei A. (Frontiers in Immunology, 2021)
TNF is a multifunctional cytokine with its key functions attributed to inflammation, secondary lymphoid tissue organogenesis and immune regulation. However, it is also a physiological regulator of hematopoiesis and is involved in development and homeostatic maintenance of various organs and tissues. Somewhat unexpectedly, the most important practical application of TNF biology in medicine is anti-TNF therapy in several autoimmune diseases. With increased number of patients undergoing treatment with TNF inhibitors and concerns regarding possible adverse effects of systemic cytokine blockade, the interest in using humanized mouse models to study the efficacy and safety of TNF-targeting biologics in vivo is justified. This Perspective discusses the main functions of TNF and its two receptors, TNFR1 and TNFR2, in steady-state, as well as in emergency hematopoiesis. It also provides a comparative overview of existing mouse lines with humanization of TNF/TNFR system. These genetically engineered mice allow us to study TNF signaling cascades in the hematopoietic compartment in the context of various experimental disease models and for evaluating the effects of various human TNF inhibitors on hematopoiesis and other physiological processes.